Bibliometrično-bibliografska primerjava revije Železarski zbornik (1967/1968) in Kovine zlitine tehnologije (1996/1997) - Jamar, Nina (Materiali in tehnologije, 2000)
In this paper the results of bibliometric analysis of the journal Kovine zlitine tehnologije vo. 30, 31 (1996, 1997) in comparison with the journal Železarski zbornik vol. 1, 2 (1967, 1968) as it was named previously, are discussed. The results show the development of the journal and progress in quality in these years. Analyzing with bibliometric methods we establish that: -the number of authors and also the number of institutes is increasing; -the fields of work dealt with in a journal have extended; -the professional journal has become scientific journal.
Keywords: bibliometrija; bibliometrična analiza; Kovine zlitine tehnologije (periodična publikacija); Železarski zbornik (periodična publikacija)